2010
DOI: 10.1366/000370210792081127
|View full text |Cite
|
Sign up to set email alerts
|

Complexation of Europium(III) with the Zwitterionic Form of Amino Acids Studied with Ultraviolet—Visible and Time-Resolved Laser-Induced Fluorescence Spectroscopy

Abstract: The complex formation of europium(III) with the zwitterionic form of amino acids (alanine, phenylalanine, and threonine) has been studied in aqueous solution. Measurements were performed at I = 0.1 M (NaCl/NaClO(4)), room temperature, and trace metal concentrations in the range of pH 2 to 8 using ultraviolet-visible (UV-Vis) and time-resolved laser-induced fluorescence spectroscopy (TRLFS). While complexation leads to a significant luminescence enhancement in the emission spectrum of the metal ion, absorption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…Transition metals including rare earth metals are able to form a diversity of complexes with organic compounds bearing groups that are Lewis bases. Alanine is not an exception, and a number of its complexes with lanthanides [14][15][16][17][18][19] and actinides [20][21][22] have been reported. Three main types of complexation between amino acids and lanthanides are known ( Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Transition metals including rare earth metals are able to form a diversity of complexes with organic compounds bearing groups that are Lewis bases. Alanine is not an exception, and a number of its complexes with lanthanides [14][15][16][17][18][19] and actinides [20][21][22] have been reported. Three main types of complexation between amino acids and lanthanides are known ( Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Similar results were obtained via Heller et al in complexation of alanine with Europium (III) in water. They also showed that the complex stability constants of the carboxyl group of side chain aspartic and glutamic acid with Europium (III) ion were high [42].…”
Section: Discussionmentioning
confidence: 99%
“…Also, Saffar et al showed that a mutated SmtA protein could absorb cadmium ions [24]. In addition, experiments on ion Europium (III) absorption with the zwitterion form of amino acids by means of UV-Vis spectroscopy were studied by Heller et al [42]. Then ionic absorption of proteins can be studied by theoretical and experimental methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the emission spectrum of the Cm 3þ aqua ion peaks at 593.5 nm, 27,29,[44][45][46] this means a red shift of the curium(III) luminescence wavelength in human urine with pH e5.8. Time-resolved measurements exclusively yielded monoexponential decay curves in urine samples with pH e5.8.…”
Section: Curium(iii) and Europium(iii) Complexation With Modelmentioning
confidence: 99%